A novel Co(II) complex with sulfamethoxazole ligand: isostructuralism, non-covalent interactions, Hirshfeld surfaces, crystal voids and energy calculations - Di Santo, Alejandro (2025)
The crystal structure of [Co(H₂O)₆][Co(SMX)₃]₂ complex (SMX = sulfamethoxazole), hereafter CoSMXW, has been solved by X-ray diffraction methods. The complex CoSMXW was characterized by Infrared (IR), Raman, and UV-Vis spectroscopies. A comparison with the analogous Mn(II) complex, [Mn(H₂O)₆][Mn(SMX)₃]₂ (CSD refcode AJIFUW), indicates 3D isostructurality and packing similarity, as evident from X-ray diffraction and geometric descriptors such as dissimilarity index (X = 2.0 from XPac) and packing similarity (PSab = 0.3070 from CrystalCMP), respectively. This represents the first case of isostructurality observed among eleven metal complexes of sulfamethoxazole reported in the literature. A study of non-covalent interactions shows presence of structural motifs involving N-H…O and N-H…S (Motif I), N-H…O (Motif II), O-H…O and O-H…N (Motif III) H-bonds, as well as C-H…π contacts (Motif IV) for [Co(H₂O)₆][Co(SMX)₃]₂ and AJIFUW. Energy analysis using CrystalExplorer indicates that the strongest dimer involves Motifs I and II with total energy of -70.3 kcal/mol for CoSMXW, which is only 2.1 kcal/mol longer than that for AJIFUW. Hirshfeld surface (HS) analysis reveals meaningless effect of metal replacement on the intermolecular contacts, confirming the energetic results. The volume of the crystal voids and the percentage of free space were calculated as 862.35 Å³ and 11.8 % for CoSMXW, and 911.42 Å³ and 12.2 % for AJIFUW. 3D topology and hierarchy of interactions were analyzed with energy framework diagrams. Further, structural motifs, HS, crystal voids and intermolecular energies for the SMX free ligand (CSD refcode SLFNMB08) were also studied. Finally, the present study was complemented with DFT calculations to evaluate the strength and nature of the non-covalent interactions by using the quantum theory of atoms in molecules (QTAIM) and NCIplots computational tools. In addition, we have used the potential energy density predictor obtained from QTAIM analysis to investigate the relative contribution of each interaction to the formation of the assemblies.